2013
DOI: 10.1002/adfm.201302631
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Mesoporous Carbon Promoted Chemical Adsorption of Sulfur and Fabrication of High‐Areal‐Capacity Sulfur Cathode with Exceptional Cycling Stability for Lithium‐Sulfur Batteries

Abstract: As one important component of sulfur cathodes, the carbon host plays a key role in the electrochemical performance of lithium‐sulfur (Li‐S) batteries. In this paper, a mesoporous nitrogen‐doped carbon (MPNC)‐sulfur nanocomposite is reported as a novel cathode for advanced Li‐S batteries. The nitrogen doping in the MPNC material can effectively promote chemical adsorption between sulfur atoms and oxygen functional groups on the carbon, as verified by X‐ray absorption near edge structure spectroscopy, and the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
594
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 919 publications
(613 citation statements)
references
References 58 publications
10
594
2
2
Order By: Relevance
“…Doping carbon with nitrogen is an alternative method to enhance the chemisorption towards LiPSs without compromising the conductivity. 35 Song et al has introduced a mesoporous N-doped carbon with high surface area (824…”
Section: Polar-polar Chemical Interactions With Polysulfidesmentioning
confidence: 99%
“…Doping carbon with nitrogen is an alternative method to enhance the chemisorption towards LiPSs without compromising the conductivity. 35 Song et al has introduced a mesoporous N-doped carbon with high surface area (824…”
Section: Polar-polar Chemical Interactions With Polysulfidesmentioning
confidence: 99%
“…The calculation is based on the following reaction: coronene_OH+S n 2 − → (coronene_S n ) − +OH − (n = 1, 2, 4, 6, 8) This model was used to represent the terminal edges of the GQDs, and we attached a hydroxyl group (-OH) to one of the edges of the carbon atoms, 'coronene_OH'. 37 A coronene is a polycyclic aromatic hydrocarbon comprising six peri-fused benzene rings with the chemical formula C 24 H 12. Moreover, the coronene model is composed of small sp 2 clusters and is isolated by sp 3 carbon, which is close to individual GQDs without oxygen functional groups, and it has been previously employed as a reduced model of graphene for quantum calculations in lithium-sulfur battery studies. 37,38 The relative energies calculated by DFT for the reactants and products indicate that replacing the terminal hydroxyl group by a sulfur dianion results in a lower energy state.…”
Section: Electrochemical Tests For Li-s Batteriesmentioning
confidence: 99%
“…37 A coronene is a polycyclic aromatic hydrocarbon comprising six peri-fused benzene rings with the chemical formula C 24 H 12. Moreover, the coronene model is composed of small sp 2 clusters and is isolated by sp 3 carbon, which is close to individual GQDs without oxygen functional groups, and it has been previously employed as a reduced model of graphene for quantum calculations in lithium-sulfur battery studies. 37,38 The relative energies calculated by DFT for the reactants and products indicate that replacing the terminal hydroxyl group by a sulfur dianion results in a lower energy state. The relative energies are shown in Figure 5, where it is clear that the energies of the product decrease when sulfur dianions are replaced with the terminal hydroxyl group.…”
Section: Electrochemical Tests For Li-s Batteriesmentioning
confidence: 99%
“…Song et al (2014) reported the interaction between nitrogen, oxygen, and sulfur in sulfur cathodes. With the use of X-ray absorption near edge structure spectroscopy (Figure 3), the authors determined that nitrogen-doping enable more sulfur accessible to oxygen functional groups on carbon, which is considered as a key role in sulfur immobilization.…”
Section: Nitrogen-doped Meso-and Microporous Carbonmentioning
confidence: 99%
“…Oxygen K-edge XANES spectra and (B) molecule simulation of mesoporous nitrogen-doped carbon (MPNC) and MPNC-sulfur nanocomposites (Song et al, 2014). The synthetic strategy relies on two steps: (1) growing N-CNTs or N-CNFs with C and N containing precursor; and (2) creating porous N-CNT or N-CNFs through carbon activation processes.…”
Section: Figure 3 | (A)mentioning
confidence: 99%